Developement of the Centers of Vocational Education in Latvia - Kiris, Kaspars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this study was to find impact factors and results of stuctural reforms of vocational education in Latvia. The objective was to find that during 4 years period reforms started as planned, but did not continued planned way. It may impact vocational education of Latvia in future. This study used analysis of 12 documents impacting reforms. One of basic results is creating Centers of Competence of vocational education. Findings are focused on creating factors and results of these centers. Author shows purposes and criterias of reforms, development on time axis, and results and impact factors of creation of the Centers of Vocational Education, gives suggestions for further reforms.